Desenvolvimento, caracterização e avaliação da atividade antitumoral em células de adenocarcinoma mamário humano de nanocápsulas poliméricas contendo derivados de isatina - Formiga, Allessya Lara Dantas (2025)
Breast cancer is one of the most common and lethal tumor types worldwide. Due to its high heterogeneity, tumor cells can develop resistance mechanisms against oncological treatments. Therefore, the use of isatins has gained prominence due to their antiproliferative activity, especially when incorporated into advanced nanocarrier systems that enhance tumor endocytosis. This study aimed to develop, characterize, and evaluate the antitumor activity of polymeric nanocapsules (PNCs) containing isatin derivatives against mammary adenocarcinoma cells. The isatins (ISA7d, ISA8d, and ISA11d) were characterized by FTIR spectroscopy to identify functional groups, and their maximum absorbance regions were determined by ultraviolet spectroscopy. The quantification methods were validated using HPLC-UV, demonstrating linearity, specificity, accuracy, precision, and robustness. Solubility and partition coefficient analyses indicated that ISA8d (logP >1.05) had a higher partition coefficient in medium-chain triglycerides (MCT) compared to ISA7d (>0.80) and ISA11d (>0.78), with degradation occurring after 30 days, especially at lower temperatures (4°C). PNCs were produced using the nanoprecipitation method and optimized through a Box-Behnken experimental design, considering PCL (50, 100, 150 mg), MCT (50, 175, 300 mg), and Kolliphor®ELP (20, 60, 100 mg) as independent variables. The optimized formulation exhibited a particle size of 239.8 ±1.3 nm, a PdI of 0.12±0.02, and a zeta potential of -20.1±0.4 mV. Kolliphor®ELP significantly reduced particle size (R²=0.985). Subsequently, PNCs were functionalized with chitosan (qPNCs) and Lipoid-PEG (pPNCs), leading to charge inversion and system neutralization, respectively, without significant changes in particle size. The incorporation of isatins did not alter the physicochemical parameters of the PNCs, with infrared spectra suggesting successful encapsulation while maintaining a spherical and uniform morphology, as confirmed by surface analysis. Encapsulation efficiency was above 97.2% for all formulations, despite low drug content (<130.1 μg/mL). Stability tests revealed no significant changes in samples stored at 4°C for 90 days. The PNCs demonstrated good stability with albumin, forming complexes independent of concentration, except for pPNCs, which required a higher albumin concentration (>20 mg/mL). In vitro cytotoxicity assays using MTT indicated that qPNCs exhibited the highest toxicity against human breast adenocarcinoma cells (MCF-7), with ISA7d, ISA8d, and ISA11d showing IC50 values above 7.34 μg/mL, with cell death associated with the JNK pathway. Thus, stable and functionalized PNCs were successfully developed, demonstrating distinct albumin interaction profiles and high anticancer efficacy, highlighting their potential as drug delivery systems.